Activation of rat brain phospholipase D by ADP-ribosylation factors 1,5, and 6: separation of ADP-ribosylation factor-dependent and oleate-dependent enzymes. - Massenburg, D (1994)
Two major forms of phospholipase D (PLD) activity, solubilized from rat brain membranes with Triton X-100, were separated by HPLC on a heparin-5PW column with buffer containing octyl glucoside. One form was completely dependent on sodium oleate for activity. The other, which was dramatically activated by the addition of ADP-ribosylation factor (ARF) 1 and guanine 5' [gamma-thio]triphosphate, required the presence of phosphatidylinositol 4,5-bisphosphate in the phosphatidylcholine substrate for demonstration of activity, as described by others. Oleate-dependent activity was unaffected by guanine 5' [gamma-thio]triphosphate, or phosphatidylinositol 4,5-bisphosphate. Both sodium oleate-and ARF-dependent activities catalyzed transphosphatidylation, thus identifying them as PLDs. ARF-dependent PLD was activated by recombinant ARF5 (class II) and ARF6 (class III), as well as ARF1 (class I). Myristoylated recombinant ARFs were more effective than their nonmyristoylated counterparts. ARFs were originally identified as activators of cholera toxin ADP-ribosyltransferase activity. The effects of recombinant ARF proteins from the three classes on cholera toxin activity (assayed under conditions identical to those used to assay PLD activity) did not, however, correlate with those on PLD, consistent with the notion that different aspects of ARF structure are involved in the two functions.